Early Diagnosis of Acquired von Willebrand Syndrome (AVWS) is Elementary for Clinical Practice in Patients Treated with ECMO Therapy - Schmidt, Rene; Zieger, Barbara; Rosenfelder, Simone; Kalbhenn, Johannes; Schelling, Johannes; Nakamura, Lea (Journal of Atherosclerosis and Thrombosis, 2015)
Aims: Acquired Von Willebrand syndrome (AVWS) is an acquired bleeding disorder that has been reported to aggravate bleeding complications in patients with ventricular assist devices or aortic stenosis. AVWS is characterized by the loss of the high-molecular-weight (HMW) multimers of Von Willebrand factor (VWF) with consequent impaired VWF binding to platelets and collagen. The aim of this study was to investigate the development of AVWS in patients treated with veno-venous ECMO (extracorporeal membrane oxygenation) support. Methods: We examined the presence of AVWS in adult patients receiving ECMO support (n=18) and control subjects treated without ECMO support (n=18). The diagnosis of AVWS was made based on the ratio of collagen-binding capacity to VWF-antigen (VWF:CB/VWF:Ag) and a VWF multimeric analysis. In addition, bleeding episodes were monitored. Results: All patients supported with ECMO developed AVWS. AVWS was identified in the early period after ECMO implantation, i.e. within 24 hours after ECMO implantation. In 17 patients, the VWF:CB/VWF:Ag ratio was significantly reduced and HMW multimers were severely missing, and 17 of the 18 patients developed bleeding complications and required transfusions of blood, FFP and/or platelet concentrates.In addition, nine patients without an ECMO device were investigated (prior to ECMO implantation: n=2, after ECMO explantation: n=7). Conclusions: In this study, all patients treated with ECMO support developed AVWS, and AVWS was detectable within 24 hours after ECMO implantation. However, the AVWS was reversible after ECMO explantation. Making an early diagnosis of AVWS and providing appropriate treatment may reduce the incidence of life-threatening bleeding.